WOMAN REPRESENTATION AND PSYCHOPATHIC RECONSTRUCTION IN "GONE GIRL" FILM - Ahmad Murdani (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of the study is to shows how the women representation and psychopathic reconstruction in the “Gone Girl” film. The technique of collecting data is observing the film then captured some of the images in the scene that was found the element of a sign that women representation women and reconstruction of a psychopath. The data that was already collected then analyzed in order with the methods narrative. The conclusions of this study, in the Gone Girl movie, show signs that women representation and psychopathic reconstruction, that women are strong and able to resist, intelligent and able to think and can do anything if they disturb them, unlike women who are usually graceful and charming. Keywords: woman representation; psychopathic; film analysis.